Participatory Budgeting: Diffusion and Outcomes across the World - Wampler, B.; Hartz-Karp, Janette (Dept. of Political Science ,Auburn University, US, 2012)
In this special issue of the Journal of Public Deliberation, multiple faces of Participatory Budgeting programs are revealed. The articles demonstrate that there is no standardized set of “best practices” that governments are adopting, but there are a broader set of principles that are adapted by local governments to meet local circumstances. Adopt and adapt appears to be the logic behind many PB programs.